2014
DOI: 10.1111/ahg.12058
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variants in theMC4RandLEPRGenes among Severely Obese Children from the Iberian Population

Abstract: SummaryWe screened for mutations in the MC4R and LEPR genes and investigated the genotype-phenotype correlation in obese individuals belonging to families with evident hereditary patterns of severe and early-onset obesity among the Iberian population.A total of 202 unrelated and severely obese patients since childhood, were enrolled in the study. Bidirectional sequencing of the MC4R gene was carried out in all patients; the LEPR gene was sequenced in 15 individuals based on additional clinical signals. Segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In Hispanics, G323E previously reported in Iberians, was also detected in three Hispanics including an obese pediatric individual ( Supplementary Table S2), [36]. I269N is another known pathogenic variant exclusively seen in Hispanic ethnicity with penetrance of 100% for obesity in our collection ( Supplementary Table S2) [15].…”
Section: Discussionsupporting
confidence: 58%
“…In Hispanics, G323E previously reported in Iberians, was also detected in three Hispanics including an obese pediatric individual ( Supplementary Table S2), [36]. I269N is another known pathogenic variant exclusively seen in Hispanic ethnicity with penetrance of 100% for obesity in our collection ( Supplementary Table S2) [15].…”
Section: Discussionsupporting
confidence: 58%
“…Notably, variant pathogenicity interpretation can evolve over time; new clinical, genetic, or functional data may influence pathogenicity calls and result in differences between labs. For example, the genetics lab used for this study reported the PCSK1 (ClinVar ID 14040) variant as “risk” and the LEPR (ClinVar ID 631614) variant as uncertain which is discrepant from current ClinVar reports [ 29 , 30 , 36 51 ] (Supplementary Table 2 ), highlighting the importance of variant reanalysis. Without extensive efforts to provide genetic and functional evidence of variant effect, such as segregation analysis to establish inheritance patterns, more extensive examination of phenotypic characteristics, assessment in physiologically relevant experimental systems, and transcriptomic analysis of subject biospecimens, interpretation of whether these variants of uncertain significance do or do not impart risk for obesity is limited.…”
Section: Discussionmentioning
confidence: 71%
“…In total, 5175 records were screened (Fig. 1), of which 24 records presented unique patients with LepR deficiency and were eligible for inclusion (2,4,5,7,9,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35). From these 24 records, we identified n = 86 unique patients with LepR deficiency from 57 different families.…”
Section: Systematic Literature Search and Overview Of Published Casesmentioning
confidence: 99%